MUSIK BIA: FUNGSI DAN REALITAS SOSIAL PADA MASYARAKAT DI KABUPATEN MINAHASA UTARA - Richard Junior Kapoyos (Tonika: Jurnal Penelitian dan Pengkajian Seni, 2018)
The Phenomenon of Bia Music in Batu village community needs to be closely examined considering that the Bia Music in the past to the present time is shifting and changing, due to lack of awareness, people's behavior towards Mia Music. The music of this tradition is very apprehensive to see the reality of the players from year to year diminishing in quantity and quality. The purpose of this research is to analyze: (1) Function of Bia Music, (2) Social reality that happened in society. This research uses qualitative method with data collection technique of interview, observation and document study. The technique of data validity is based on the credibility criteria, using triangulation of data. Data analysis techniques used are data collection, data presentation, data reduction, and data verification. The results of this study indicate that the Functions of Bia Music, among others, as a medium of ritual, communication media, into evangelism media, events of cultural festivals, education, association, entertainment and publicity. There are three moments of dialectics in the social realities of externalization, objectivity, and internalization.